The incidence and management of hypotension in the pregnant parturients undergoing caesarean section following spinal anaesthesia with 0.5% bupivacaine - Minj, Shashi Dinkar; Beck, Rameshwari; Kumar, Ajit; Tiwari, Praveen; Chandan, Raj Kumar; Sen, Sukanta (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Spinal anesthesia for cesarean section is not a 100% successful technique. At times, despite straightforward insertion and drug administration, intrathecal anaesthesia for cesarean section fails to obtain any sensory or motor block. Methods: This study is aimed at comparing the incidence of hypotension and the need for vasopressors in patients submitted to caesarean section under spinal anaesthesia following preload with either crystalloid or colloid. This study was carried out on 100 healthy pregnant women with single term foetus and not in labor admitted at the labor room of Gynecological department of RIMS. Blood pressure, Pulse rate, O2 Saturation and episodes of hypotension were recorded every 5 minutes from the spinal block. Results: The study showed that maximum number of caesarean sections here performed for the indication of foetal distress which is seen in 44%, 48%, 52%, and 48% in Group A, Group B, Group C and Group D respectively. This is followed by scar tenderness and obstructed labour. In Group A maximum number of patients developed hypotension during 11-20 minutes duration which is 13 (61.9%) followed by 5 (23.8%) patients during first 10 minutes. Conclusions: The study concludes that the combined use of volume preloading to compensate for vasodilatation and vasopressor to counteract arterial dilatation is a very effective method in reducing the incidence, severity and duration of spiral hypotension. The combination group with decreased volume of preload and reduced dose of vasoconstrictor provides better haemodynamic stability when compared to preloading of vasoconstrictors alone.